Preparation and characterization of Li and Ti codoped NiO nanocomposites for gas sensors applications - (:unkn) unknown (ELSEVIER SCIENCE SA, 2009)
This work investigated the use of Li and Ti codoped NiO nanocomposites as a room temperature (R-T) gas sensor. The nanocomposites were prepared using citrate-gel technique. In order to reduce agglomeration, the polyvinyl alcohol was added as a reducing agent. The thermal analysis of gel composition of Li0.1Ti0.018Ni0.882O (LTNO) was investigated by DTA/TG and phase evolution of as-burnt powder was examined by XRD technique. XRD showed single phase NiO at 500 degrees C. TEM investigation revealed that the size of particles ranged from 5 to 40 run. To detect sensor response, final sample was dissolved with minimum amount of solvent anti spin coated thin film onto glass substrate with interdigitated gold (Au) electrodes. The film was used to detect toluene, ethanol and chloroform at RT. The maximum sensitivity was obtained for toluene vapors at R-T. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Nanocomposite materials; Citrate-gel processing; Gas sensors; Li-Ti-NiO; LIQUEFIED PETROLEUM GAS; ELECTRICAL-PROPERTIES; SENSING PROPERTIES; ROOM-TEMPERATURE; DOPED NIO; CERAMICS; FILMS; LIXNI(1-X)O; NIFE2O4